Fostering Reading Motivation in Self-Contained Classrooms for Students with Emotional and Behavioral Disorders - Cornell, Heidi R. (Journal of the American Academy of Special Education Professionals, 2018)
This study sought to explore and describe the extent to which research based practices were employed for cultivating an environment that fostered reading motivation in self-contained classrooms for students with emotional and behavioral disorders (EBD). To accomplish this, a descriptive multiple case study design was employed in which data were collected in three self-contained elementary classrooms for students with EBD. Findings suggested that the environment for learning in these classrooms has likely not changed much since Jane Knitzer’s classic study in 1990. This study serves as a call to researchers and teacher educators to increase attention on the education and treatment of children and youth with EBD being served in self-contained classrooms.